Kajian Pengaruh Capital Adequacy Ratio, Dana Pihak Ketiga, Loan to Deposit Ratio dan Net Interest Margin terhadap Penyaluran Kredit pada Perusahaan Sub Sektor Perbankan di Bursa Efek Indonesia - Tanto Tanto (LPPM Universitas Widya Dharma Pontianak, 2022)
Credit has a very important role in the economy of a country because it is part of the intermediation function that must be carried out by banks which greatly influences the economic growth of a country. But on the other hand, banks are also faced with risks in providing credit, namely the risks suffered by banks as a result of non-payment of loans that have been given by banks to borrowers or debtors. This study was conducted with the aim of finding empirical evidence of the effect of capital, liquidity and profitability on lending. The population used in this study is the banking sub-sector companies on the Indonesia Stock Exchange. Sampling was done by purposive sampling method. Furthermore, hypothesis testing is done by multiple regression analysis. The results of the study are capital adequacy ratio has no effect on credit distribution, third party funds have a positive effect on credit distribution, loan to deposit ratio has a positive effect on credit distribution, and net interest margin has a positive effect on credit distribution.Keywords: capital adequacy ratio, third party funds, loan to deposit ratio, net interest margin, credit distribution.